A new strategy for electrochemical fabrication of manganese dioxide coatings based on silica nanoparticles deposited on titanium fibers for selective and highly efficient solid-phase microextraction. (8th March 2019) - Wang, Ziyi; Wang, Feifei; Zhang, Rong; Wang, Zuo; Du, Xinzhen
Abstract : Electrochemical fabrication of a novel Ti@TiO2 @SiO2 NPs@MnO2 /PPyNPs fiber and its application in solid-phase microextraction coupled to HPLC-UV. Abstract : A new strategy was proposed for the electrochemical fabrication of manganese dioxide (MnO2 ) coatings on titanium (Ti) fibers. In order to achieve stable MnO2 coatings, a Ti wire was initially anodized in methanol/water containing fluoride ions for the in situ growth of nano/submicro-scale titania (TiO2 ) pyramids. Thereafter, silica nanoparticles (SiO2 NPs) were electrophoretically deposited on the TiO2 coatings. Finally, the nanoparticle-like MnO2 coating was homogeneously formed on the Ti@TiO2 @SiO2 NPs fiber support in neutral electrolytic solution by cyclic voltammetry using polypyrrole as an organic binder. The resulting fiber showed good extraction selectivity and efficient extraction capability for aromatic compounds with large delocalized π-systems. For this purpose, this fiber was used for the selective enrichment of the studied polycyclic aromatic hydrocarbons (PAHs) coupled to high-performance liquid chromatography with ultraviolet detection. The linear calibration curves were obtained in the concentration range of 0.01–500 μg L −1 with correlation coefficients higher than 0.999 in all instances. The relative standard deviations (RSDs) for single fiber repeatability varied from 4.7% to 5.5% for intra-day and inter-day measurements ( n = 5), and RSDs for the fiber-to-fiber reproducibility varied from 5.8% to 6.7% ( n = 5). The developed method was successfully applied to the selective enrichment and sensitive determination of target PAHs in river water, rain water and wastewater samples with relative recoveries from 93.0% to 106%. Furthermore, the fabricated fiber was stable enough to perform the whole analytical sequence in practical applications.